Implementation of a Radiation Safety Management System in Conventional Spaces in the Radiology Installation - Wirajaya, I Wayan Angga; Diartama, Anak Agung Aris; Jeniyanthi, Ni Putu Rita; Sari, Putu Aulia Kartika (Jurnal Ilmiah Manajemen Kesatuan, 2024)
Klungkung Regional General Hospital is one of the health services owned by the Klungkung district government in the form of a hospital, managed by the Klungkung district government and recorded as a type B hospital. At the Klungkung Regional General Hospital, there are several things that are not in accordance with the radiation safety management system determined by BAPETEN. Some of these things that are not suitable such as the lack of compliance of radiation workers with the standard operating procedures (SOPs) of radiation work in conventional rooms which are often found things outside the provisions, the use of equipment such as aprons and there are doors in the radiological examination room that have leaks, because environmental exposure measurements have been made in the area and leaks were found, and also monitoring the health of radiation workers who have not been optimal. This type of research uses descriptive qualitative research methods with an observational approach from the routine activities of radiation workers at the Radiology Installation of the Klungkung Regional General Hospital. The Radiology Installation of the Klungkung Regional General Hospital has met the BAPETEN Perka standard No.4 of 2020 but there are still some that have not met the standards for the Implementation of the Radiation Safety Management System in the Conventional Room at the Radiology Installation of the Klungkung Regional General Hospital, including the conventional room inspection door to the operator room experiencing a leak, it has been reported to the relevant party in this case for follow-up so that the detected radiation leak can Dealt with immediately.